Ekomisiologi integral: Dialektika teologis mandat penciptaan dengan amanat agung Kristus dalam Markus 16:15 - Pandensolang, Welly; Agatha, Krista (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2026)
This article examines the theological relationship between the Creation Mandate (Gen. 1:28) and the Great Commission of Christ in Mark 16:15 through the lens of integral ecomissiology. Employing a biblical-theological method combined with hermeneutical and ecological analysis, this study argues that the phrase